Penerapan Metode Moving Average dan Exponential Smoothing pada Peramalan Produksi di PT. Mada Wikri Tunggal - Jidan Ahmad Danil; Sukanta Sukanta (Jurnal Ilmiah Wahana Pendidikan, 2022)
A common problem faced by managers is how to forecast future sales of goods. The use of forecasting techniques is one solution to overcome this problem. Knowing future production predictions can certainly help companies prepare company strategies for the future. This study uses the method of Moving Average 3 months and 5 months while Exponential Smoothing α= 0.1; α=0.5; α= 0.9 which aims to predict future conditions using a collection of past data, comparing the smallest error rate, then the forecasting method chosen is the Exponential Smoothing method α= 0.9 with a Mean Absolute Deviation value (MAD) of 57,7 and Mean Square Error (MSE) of 4.476,34. From the results of the analysis of data processing that has been carried out based on the selected forecasting method, that consumer demand at PT.Mada Wikri Tunggal for January 2021 with the Exponential Smoothing method α= 0.9 of 4.144,4 pcs.